Legal Protection of Workers from Unfair Practices in the Workplace considering Digital Transformation: A Study Based on the Provision of the Saudi Labor Law - Reem Saad Ali Al-Malki; Amal Mohammed Shalabi Khadragey (International Journal of Law Research and Studies, 2025)
This study addresses the legal protection of workers from unfair practices in the workplace amid digital transformation. The Saudi regulator has given significant attention to this issue by enacting and continuously developing regulations. However, violations by some employers, such as the infringement of labor laws, persist. The problem of the study lies in identifying the most prominent of these practices and analyzing the effectiveness of the provisions of the Saudi Labor Law in addressing them, while highlighting the challenges in the practical application of the established protective measures. Additionally, the study examines the role of digital transformation and the efforts of the relevant authorities in mitigating unfair practices and enhancing compliance with laws and decisions. The study is divided into a preliminary section and two main sections. The preliminary section discusses the nature of unfair practices against workers in the workplace, identifying their concept and the consequences of their existence. The first section focuses on the legal protection of workers, including the guarantees provided by the Saudi Labor Law to protect wages and the guarantees established to protect them from employer abuse when imposing disciplinary penalties. The second section discusses the role of digital transformation and digital platforms in enhancing the legal protection of workers, analyzing the impact of recent amendments to the Labor Law and its executive regulations, while clarifying the role of the relevant authorities.The study concludes with several findings, the most important of which are: The provisions of the Saudi Labor Law help reduce unfair practices by establishing legal guarantees for wage protection, regulating disciplinary penalties, and governing contractual relationships. Digital transformation strengthens these protections by documenting contracts and facilitating legal proceedings. However, there remains a need for continued review and development of certain provisions to achieve more efficient and comprehensive protection. The study also concludes with several recommendations, the most prominent of which is: a recommendation to the Saudi regulator to establish a fixed time frame for resolving labor disputes, particularly when the employee is the claimant, to ensure the swift alleviation of harm, considering the duration of the conciliatory process that precedes it.
Keywords: Unfair Practices; Legal Protection; Saudi Labor Law; Digital Transformation; Labor Court